The Relationship between the Shareholders Structure and Board of Directors Structure at the Stock Exchange of Thailand - Papangkorn, Attawoot (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research paper focuses on the study of the Board of Directors as the key persons in overseeing the rights of shareholders and defining the level of transparency for the company. According to the practices in corporate governance, the research paper uses the cross-sectional data from listed companies in the Stock Exchange of Thailand. Eleven years of data, from 2002-2012, of the database from SETSMART and SET was used to calculate a statistical relationship between the structure of shareholders and board of directors through economic analysis. Various tools were employed, namely descriptive analysis and the fixed effect regression model. The paper has found that the shareholder structure as an independent variable and board of directors in listed companies as a dependent variable have a relationship at a significant level. Even though not all hypotheses in the research paper were accepted, the paper can conclude that there is a significant relationship between shareholder structure and board of directors.